Audit TI Kinerja Manajemen PT. X Dengan Frame Work Cobit 4.1 - Ade Ambara Putra, I Putu; Sukarsa, I Made; Agung Bayupati, I Putu (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.1 April 2015, 2015)
The development of information technology is now widely used by companies of airport to improve service to customers. The use of such technology to facilitates of information, communication, and banking transactions. The use of information technology in the operations of PT. X have many risks. The Risks that exist on the PT. X requires the existence of information technology governance to minimize it. The objective is to obtain information regarding the level of IT maturity and gaps. The framework used is COBIT 4.1. The  Results found the maturity level on the current state is level 3 and the expected conditions to be reached is level 5. The analysis carried out on the gap and then made a recommendation strategies to existing gaps, so that the level of maturity that expected to be achieved. To minimize the gap maturity level, need the suggestions for improvement that taken from the high control objectives COBIT 3rd edition. The importance level give the process is a standard model, among others Critical Sucess Factor (CSF), indicators such as the Key Goal Indicators (KGI) and Key Performance Indicator (KPI).
Keywords: Teknologi Informasi, COBIT 4.1, Tingkat Kematangan, Tingkat Kepentingan, Audit